Modelling metastatic colonization of cholangiocarcinoma organoids in decellularized lung and lymph nodes - van Tienderen, Gilles S.; van Beek, Marije E. A.; Schurink, Ivo J.; Rosmark, Oskar; Roest, Henk P.; Tieleman, Jantine; Demmers, Jeroen; Muntz, Iain; Conboy, James; Westergren-Thorsson, Gunilla; Koenderink, Gijsje; van der Laan, Luc JW; et al. (Frontiers in Oncology, 2023)
Cholangiocarcinoma (CCA) is a type of liver cancer with an aggressive phenotype and dismal outcome in patients. The metastasis of CCA cancer cells to distant organs, commonly lung and lymph nodes, drastically reduces overall survival. However, mechanistic insight how CCA invades these metastatic sites is still lacking. This is partly because currently available models fail to mimic the complexity of tissue-specific environments for metastatic CCA. To create an in vitro model in which interactions between epithelial tumor cells and their surrounding extracellular matrix (ECM) can be studied in a metastatic setting, we combined patient-derived CCA organoids (CCAOs) (n=3) with decellularized human lung (n=3) and decellularized human lymph node (n=13). Decellularization resulted in removal of cells while preserving ECM structure and retaining important characteristics of the tissue origin. Proteomic analyses showed a tissue-specific ECM protein signature reflecting tissue functioning aspects. The macro and micro-scale mechanical properties, as determined by rheology and micro-indentation, revealed the local heterogeneity of the ECM. When growing CCAOs in decellularized lung and lymph nodes genes related to metastatic processes, including epithelial-to-mesenchymal transition and cancer stem cell plasticity, were significantly influenced by the ECM in an organ-specific manner. Furthermore, CCAOs exhibit significant differences in migration and proliferation dynamics dependent on the original patient tumor and donor of the target organ. In conclusion, CCA metastatic outgrowth is dictated both by the tumor itself as well as by the ECM of the target organ. Convergence of CCAOs with the ECM of its metastatic organs provide a new platform for mechanistic study of cancer metastasis.